Determining the ways to increase economic growth of developing and developed economies: An application with data mining and fuzzy TOPSIS - Silahtaroğlu, Gökhan; Dinçer, Hasan; Yüksel, Serhat (Springer Science and Business Media Deutschland GmbH, 2021)
This study aims to identify the influencing factors of economic growth for both developing and developed economies. Firstly, literature is reviewed, and 7 different variables are selected as leading indicators of the economic growth. In this framework, 155 developing and 31 developed economies are evaluated. After that, decision tree approach is taken into consideration and the most significant 4 variables are determined for each country group. In the final process, fuzzy TOPSIS approach is used to weigh E7 and G7 economies with respect to the economic development. The findings indicate that for developing economies, the most important determinants are foreign direct investment, interest rate, domestic credit, and research and development. On the other side, inflation, domestic credit, foreign direct investment, and unemployment play a more significant role in the economic growth of developed economies. Hence, it is recommended that developing economies should mainly focus on the strategies to attract the attention of the foreign investors and to increase research and development.
Keywords: Decision Tree; Economic Growth; Fuzzy TOPSIS